ANALISIS PENERAPAN SISTEM INFORMASI AKUNTANSI PENJUALAN DAN PENERIMAAN KAS DALAM PENGENDALIAN INTERNAL PERUSAHAAN - Dilla Reifina Dastia Putri; Purwo Atmojo; Butet Wulan Trifina (Jurnal GeoEkonomi, 2024)
The purpose of this research is to determine the implementation of the internal control system for cash receipt procedures from cash sales implemented at Puan Kopi and the effectiveness of the internal control system for cash receipt procedures from cash sales implemented at Puan Kopi. The data used is an interview source from Puan Kopi. The data analysis method uses interviews and observations with the owner of Puan Kopi in Balikpapan City. The results of the analysis show that the product operational standards (SOP) for sales and cash receipts have been prepared in detail and are sufficient to support the implementation of cash receipts from cash sales.